Ketone bodies in exercise, health and disease: Metabolic mechanisms, pathophysiology, and therapeutic implications - Yin Li; Qingyi Liu; Zhihao Jia; Bin Guo (Advanced Exercise and Health Science)
Ketone bodies (KBs) are alternative metabolic fuels predominantly produced in the liver during periods of carbohydrate restriction, prolonged fasting, or ketogenic dietary intake. Beyond energy metabolism, KBs exert pleiotropic effects by modulating cellular signaling pathways, oxidative stress, and epigenetic regulation. Recent advances have underscored the importance of ketone bodies in exercise physiology and muscle function. Excessive or impaired ketone handling underlies diabetic ketoacidosis and contributes to the pathogenesis of selected neurodegenerative, cardiovascular and neoplastic disorders. Therapeutically, ketogenic diet (KD) and exogenous ketone supplementation are being explored for their potential in treating metabolic disorders, neurodegeneration, and even malignancies. This review provides a comprehensive synthesis of the latest scientific insights into KB classification, metabolic regulation, pathophysiological roles in disease, and their emerging therapeutic applications. We critically examine recent findings on KB metabolism and discuss the mechanistic underpinnings that define their physiological and pathological relevance.